Molecular Biology of Streptococcus Mutans: A Review (Academia Journal of Medicine, 2025)
Streptococcus mutans is a gram-positive bacterium and a primary etiological agent of dental caries. Its ability to adhere to tooth surfaces and form biofilms is largely attributed to its production of extracellular polysaccharides, primarily through glucosyltransferases. The genome of S. mutans, approximately 2.0 million base pairs long, contains genes that facilitate carbohydrate metabolism, acid production, and stress response mechanisms, enabling the organism to thrive in acidic environments. This bacterium ferments sugars, particularly sucrose, to produce lactic acid, leading to the demineralization of enamel and consequent tooth decay. The regulation of virulence factors is influenced by environmental factors, including pH and nutrient availability, and is mediated through complex regulatory networks and quorum-sensing mechanisms. Advanced molecular techniques, such as gene knockout and proteomics, have been employed to unravel the pathogenicity of S. mutans and identify potential targets for therapeutic intervention. Understanding the molecular biology of S. mutans is crucial for devising effective strategies for the prevention and treatment of dental caries, highlighting its significance in oral microbiology and public health.
Keywords: Streptococcus mutans; Molecular Biology